The influence of parental education and other socio-economic factors on child car seat use - Rok Simon Mateja; Korošec Aleš; Bilban Marjan (Sciendo, 2017)
The behaviour of parents in ensuring car passenger safety for their children is associated with socio-economic (SE) status of the family; however, the influence of parental education has rarely been researched and the findings are contradictory. The aim of the study was to clarify whether parental education influences the use of a child car seat during short rides.